Dampak Aktivitas PLTU Celukan Bawang terhadap Kehidupan Sosial Ekonomi Masyarakat Pesisir Desa Celukan Bawang Kecamatan Gerokgak Kabupaten Buleleng - WIBAWA, I MADE ANGGRESMA GUNA; DARMAWAN, DWI PUTRA; WIDHIANTHINI, WIDHIANTHINI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
The Impact of Celukan Bawang Power Plant Activities on the Socio-Economic Life of the Coastal Community of Celukan Bawang Village Gerokgak District Buleleng Regency PLTU Celukan Bawang is a steam power plant that was built in Celukan Bawang Village, Gerokgak District, Buleleng Regency, Bali Province. This PLTU was built to meet the need for electrical energy in Bali which continues to increase every year along with the development of the tourism sector and digitalization in various sectors of people's lives. The purpose of this study was to analyze the impact of the PLTU Celukan Bawang activity on the social and economic life of the coastal communities of Celukan Bawang, the majority of whom work as fishermen along the coast of Celukan Bawang. This type of research is descriptive with a survey method through questionnaires and in-depth interviews with the main informants. The analysis technique of this research is descriptive percentage. The results of this study indicate the impact of the company's activities on aspects of the social and economic life of the coastal village community, the majority of whom work as fishermen. These impacts include income, education, job opportunities, and results from MSMEs in the surrounding community. Based on this research, the Celukan Bawang PLTU and the local government are expected to pay more attention to the welfare aspect, especially for the fishermen around where they are the group most affected by the company's daily activities. This can be done by providing assistance in the form of fishing gear or in the form of special trainings on a regular basis so that the fishing communities there can also experience direct benefits from the company. In addition, for the people in coastal villages to pay more attention to the educational aspects of their children.